Rapid and Sensitive Differentiating Ischemic and Hemorrhagic Strokes by Dried Blood Spot Based Direct Injection Mass Spectrometry Metabolomics Analysis. Issue 6 (9th June 2016) - Hu, Zhansheng; Zhu, Zhitu; Cao, Yunfeng; Wang, Lixuan; Sun, Xiaoyu; Dong, Jun; Fang, Zhongze; Fang, Yanhua; Xu, Xiaoxue; Gao, Peng; Hongzhi, Sun
Abstract : Cerebral infarction (CI) and intracerebral hemorrhage are lethal cerebrovascular diseases, sometimes sharing similar clinical manifestations but with distinct therapeutic strategies. Delayed treatment usually resulted in poor prognosis. A timely diagnosis report is highly warranted especially in emergency. One hundred twenty‐nine CI patients, 73 intracerebral hemorrhage (ICH) patients, and 98 controls were enrolled in this study. A direct injection mass spectrometry metabolomics approach was adopted using dried blood spot samples. This targeted metabolomics analysis focused on absolute quantitation of 23 amino acids, 26 carnitine/carnitine esters, and 22 calculated ratios parameters. Compared to the normal control group, CI and ICH showed distinct metabolite changes, respectively. For stroke differentiation, Tyr, C5‐OH/C0, Cit, Asn, Pro, Val, Arg/Orn, Leu, and Val/Phe were elevated in the CI group. On the contrary, C5:1, Phe/Tyr, (C0 + C2 + C3 + C16 + C18:1)/Cit, and Met/Leu were of lower levels in the CI group. Using regression model based on some of the above‐mentioned parameters, 79.07% of stroke patients from a new set could be definitely confirmed. This study proved the targeted metabolomics analysis was a promising tool for rapid and timely stroke differentiation.